Stanniocalcin 2 Regulates Non-capacitative Ca2+ Entry and Aggregation in Mouse Platelets - López, Esther; Gómez-Gordo, L.; Cantonero, Carlos; Bermejo, Nuria; Pérez-Gómez, Jorge; Granados, María P.; Salido, Gines M.; Rosado Dionisio, Juan A.; Redondo Liberal, Pedro C. (Frontiers in Physiology, 2018)
Stanniocalcin 2 (STC2) is a fish protein that controls body Ca2+ and phosphate metabolism. STC2 has also been described in mammals, and as platelet function highly depends on both extracellular and intracellular Ca2+, we have explored its expression and function in these cells. STC2-/- mice exhibit shorter tail bleeding time than WT mice. Platelets from STC2-deficient mice showed enhanced aggregation, as well as enhanced Ca2+ mobilization in response to the physiological agonist thrombin (Thr) and the diacylglycerol analog, OAG, a selective activator of the non-capacitative Ca2+ entry channels. Interestingly, platelets from STC2-/- mice exhibit attenuated interaction between STIM1 and Orai1 in response to Thr, thus suggesting that STC2 is required for Thr-evoked STIM1-Orai1 interaction and the subsequent store-operated Ca2+ entry (SOCE). We have further assessed possible changes in the expression of the most relevant channels involved in non-capacitative Ca2+ entry in platelets. Then, protein expression of Orai3, TRPC3 and TRPC6 were evaluated by Western blotting, and the results revealed that while the expression of Orai3 was enhanced in the STC2-deficient mice, others like TRPC3 and TRPC6 remains almost unaltered. Summarizing, our results provide for the first time evidence for a role of STC2 in platelet physiology through the regulation of agonist-induced Ca2+ entry, which might be mediated by the regulation of Orai3 channel expression.